An extreme case of galaxy and cluster co-evolution at z = 0.7. Issue 3 (23rd September 2021) - Ebeling, H; Richard, J; Smail, I; Edge, A C; Koekemoer, A M; Zalesky, L
ABSTRACT: We report the discovery of eMACS J0252.4−2100 (eMACS J0252), a massive and highly evolved galaxy cluster at z = 0.703. Our analysis of Hubble Space Telescope imaging and VLT/MUSE and Keck/DEIMOS spectroscopy of the system finds a high-velocity dispersion of 1020^+180_-190 km s −1 and a high (if tentative) X-ray luminosity of (1.2 ± 0.4) × 10 45 erg s −1 (0.1–2.4 keV). As extreme is the system's brightest cluster galaxy, a giant cD galaxy that forms stars at a rate of between 85 and 300 M⊙ yr −1 and features an extended halo of diffuse [O ii ] emission, as well as evidence of dust. Its most remarkable properties, however, are an exceptionally high ellipticity and a radially symmetric flow of gas in the surrounding intracluster medium, potential direct kinematic evidence of a cooling flow. A strong-lensing analysis, anchored by two multiple-image systems with spectroscopic redshifts, finds the best lens model to consist of a single cluster-scale halo with a total mass of (1.9 ± 0.1) × 10 14 M⊙ within 250 kpc of the cluster core and, again, an extraordinarily high ellipticity of e = 0.8. Although further, in-depth studies across the electromagnetic spectrum (especially in the X-ray regime) are needed to conclusively determine the dynamical state of the system, the properties established so far suggest that eMACS J0252 must have already been highly evolved well before z ∼ 1, making it a prime target to constrain the physical mechanisms and history of the co-evolution or dark-matter haloes and baryons in the era of cluster formation.